Prospects of Artificial Intelligence in Financial Sector in Uzbekistan - Tokhtabaev, Azizbek; Yusopov, Ibrohim; Zulkifli, Che Zalina (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: The paper discusses the usage of artificial intelligence (AI) in financial analysis in Uzbekistan, highlighting the potential benefits and challenges of AI adoption in the country's financial sector. Design/methodology/approach: The paper compares Uzbekistan's development to global experience, analyzing the current state of AI adoption in financial analysis, and identifying the major obstacles to its implementation. Findings: The findings indicate that AI has positive aspects in credit risk, fraud detection, and prediction. However, the major obstacles to AI adoption are infrastructure, regulation, and literacy. The paper proposes a gradual hybrid approach, combining regulatory support and fintech innovation, to allow systematic integration of AI. Paper type: Research paper